RESISTANCE TRAINING IN THE ELDERLY: A REVIEW OF TRAINING INTENSITY (Fiep Bulletin - online, 2012)
The loss of strength and function in the elderly has already been widely discussed in literature. Resistance training has been seen as a way of preventing or even reversing this situation. On the other hand, the area is notorious for the difficulty in prescribing the load intensity that is appropriate for the results to be effective. The aim of this study was to compare the effects of different intensities of resistance training with strength gain in the elderly. The methodology consisted of a review of the bibliography. The articles used were chosen from the following data banks: Lilacs, Medline and Scielo. The research was conducted between December 2009 and July 2010. The terms used in the study are as follows: elderly, strength training, resistance training, intensity of training. It was concluded that progressions in load and training should be carried out more slowly due to the greater difficulty in learning the proposed movements and dynamics, however, it was the higher loads that produced the most significant strength gains, so bearing in mind that ageing does not imply that it is impossible to adapt to the training, the increase in intensity becomes important in obtaining more effective results. Strength training injuries did not occur in any of the studies, which demonstrates the safety of training when conducted properly.
Keywords: elderly subjects; intensity of training; strength training